Xerosis cutis and associated co-factors in women with prurigo nodularis - Sevgi Akarsu; Ozlem Ozbagcivan; Turna Ilknur; Fatma Semiz; Burcu Bahar Inci; Emel Fetil (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Current data regarding the associated factors of prurigo nodularis are still uncertain, except for atopic predisposition. Objectives: The purposes of this study were to (1) determine the frequencies of xerosis and other accompanying diseases of female patients with prurigo nodularis; (2) compare the demographic, clinical and accompanying disease characteristics by grouping these patients according to whether they have associated xerosis (who were subsequently subgrouped as atopic or non-atopic) or not. Methods: In this retrospective descriptive study, 80 females with PN were categorized according to the accompanying diseases (dermatological, systemic, neurological, psychogenic, mixed, or undetermined origin). Results: A total of 45 associated co-factors including dermatological in 63 (78.8%), systemic in 57 (71.3%), psychological in 33 (41.3%) and neurological co-factors in 14 (17.5%) of all patients with prurigo nodularis were detected. Xerosis was observed in 48 (60%) patients (non-atopic co-factors in 66.7% of them). The ratio of patients with mixed co-factors, dermatological+systemic co-factors and dermatological+systemic+psychological co-factors were found to be significantly higher in patients with xerosis compared to those without xerosis. Study limitations: Our study has certain limitations such as the absence of an age-matched control group, absence of follow-up data and the fact that the diagnosis of xerosis has not been based on objective methods. Conclusions: Xerosis has been identified in more than half of the patients with PN and it has been determined that in most patients xerosis is associated especially with diabetes mellitus and other conditions related to prurigo nodularis.